2008
DOI: 10.1051/0004-6361:20078119
|View full text |Cite
|
Sign up to set email alerts
|

BVRIphotometric analysis for the galaxy group NGC 4410

Abstract: We present a BVRI CCD (Charge Coupled Device) surface photometry analysis of the galaxy group NGC 4410, which contains four galaxies in interaction. Along with our photometric study, we show residual images (after subtracting isophotal models) and unsharp masked images to uncover any hidden structures in this system of galaxies; we have also performed a two-dimensional bulge-disk decomposition for NGC 4410C and D, and a major axis sector profile for NGC 4410A. We have calculated BVRI surface brightnesses and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
4
4
0
Order By: Relevance
“…Galaxies C, E have a 4 /a > 0 for about 20" indicating that these isophotes are dominated by a small disk component (the mean values of a 4 /a in disk galaxies are reported as a 4 /a > 2, see Pérez-Grana et al [21], Grutzbauch et al [7], Jerjen et al [25]) this indicative is also found in our unsharp masked images and residual images.…”
Section: Optical Profiles and Spectra Of The Individual Memberssupporting
confidence: 77%
See 3 more Smart Citations
“…Galaxies C, E have a 4 /a > 0 for about 20" indicating that these isophotes are dominated by a small disk component (the mean values of a 4 /a in disk galaxies are reported as a 4 /a > 2, see Pérez-Grana et al [21], Grutzbauch et al [7], Jerjen et al [25]) this indicative is also found in our unsharp masked images and residual images.…”
Section: Optical Profiles and Spectra Of The Individual Memberssupporting
confidence: 77%
“…Along with sky subtraction we made a seeing correction to BV images applying a convolution function in order to smooth the image. The standard photometric equation used in [21] was applied in the same manner in this work. In each run observations of Landolt standard fields containing Palomar Green stars were performed during the night at a range of air-masses.…”
Section: Photometric Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that for the 2.1m telescope data we have used Landolt standards defined in the Johnson-Kron-Cousins system while the filters used for the observations are Johnson filters, and in R and I there are significant differences between the two filter systems. Pérez-Grana et al (2008) reported no significant differences between the surface brightnesses obtained over a range of galaxy colours, using previous observations of galaxies in both systems.…”
Section: Optical Ccd Photometry and Data Reductionsupporting
confidence: 54%